ナンキョク ミズホ コウゲン カラ エタ センソウ ボーリング コアー チュウ ノ サンソ ドウイタイ ノ ブンプ - 加藤, 喜久雄; カトウ, キクオ; 渡辺, 興亜; ワタナベ, オキツグ; KATO, Kikuo; WATANABE, Okitsugu (国立極地研究所, 1977)
P(論文) 南極氷床の浅層ボーリングコアーについて,酸素同位体組成および核実験による人工放射線量(総β線量)の測定と積雪層位解析を行い,積雪量の雪尺による実測や雪面観察の結果を参考にして,コアーにおける酸素同位体の垂直分布について検討した.総β線量の測定結果から判断して,コアー中の酸素同位体組成の変動が,降雪の酸素同位体組成の季節変化に基づく1年につき1周期でない地域があることがわかった.この地域では,堆雪が連続的に生ぜず,削剥,堆雪,無堆雪という堆雪環境の時間的変動と,堆雪後の積雪層内における水蒸気の移動による雪の変態の二つの因子が,コアー中の酸素同位体の分布を大きく規制していると考えられる.この二つの因子の規制のない地域でのボーリングコアー中の酸素同位体組成の変動は,1年同期になっており,上の考え方が間違いでないことが明らかにされた. Oxygen isotope, gross β-radioactivity and stratigraphic determinations were done on firn cores from Mizuho Plateau, Antarctica. Factors controlling oxygen isotope variations in firn were discussed. From the results of gross β-activity measurements, it is obvious that the cycle in oxygen isotope profile is once a year in some areas due to the seasonal variation in oxygen isotopic composition of snowfall. In other areas, the cycle is not once a year. The following two factors are considered to affect strongly oxygen isotope variations in firn, from the results of direct stake measurements of snow accumulation and observations of surface conditions of the ice sheet. 1) changes in time of erosion, deposition and none on snow surface, 2) subsequent movement of water vapor in firn. departmental bulletin paper